Fixing the Image : Ultrasound and the Visuality of Care in Phnom Penh - Grant, Jenna (Book collections on Project MUSE., 2022)
"Introduced in Phnom Penh around 1990, at the twilight of socialism and after two decades of conflict and upheaval, ultrasound took root in humanitarian and then privatized medicine. Services have since multiplied, promising diagnostic information and better prenatal and general health care. In Fixing the Image Jenna Grant draws on years of ethnographic and archival research to theorize the force and appeal of medical imaging in the urban landscape of Phnom Penh. Set within long genealogies of technology as tool of postcolonial modernity, and vision as central to skilled diagnosis in medicine and Theravada Buddhism, ultrasound offers stabilizing knowledge and elicits desire and pleasure, particularly for pregnant women. Grant offers the concept of "fixing"-which invokes repair, stabilization, and a dose of something to which one is addicted-to illuminate how ultrasound is entangled with practices of care and neglect across different domains. Fixing the Image thus provides a method for studying technological practice in terms of specific materialities and capacities of technologies-in this case, image production and the permeability of the body-illuminating how images are a material form of engagement between patients, between patients and their doctors, and between patients and their bodies"--